TYPICAL VIOLATIONS DETECTED DURING THE AUDIT OF MILITARY UNITS OF THE ARMED FORCES OF UKRAINE - Shramko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
The article considers the general principles of internal audit, the concept, essence, as well as theoretical principles and methodological features of internal audit in the military units of the Armed Forces of Ukraine. Considerable attention is also paid to the purpose of internal audit in general and in the Armed Forces of Ukraine in particular. The definition of audit and internal audit is given in accordance with the norms of current regulations of Ukraine. The process of planning, organization and direct conduct of internal audit, as well as the results of auditors’ work is described in detail, the analysis of the regulatory framework for conducting internal audit in budgetary institutions and, in particular, in the Armed Forces of Ukraine. Particular attention is paid to the stages of audit, analysis of typical violations identified in the process of internal audit and internal control. The analysis of the results of the internal audit for 2014-2019 is carried out, the typical violations revealed in the process of internal audit are given, and the violations in 2019 are considered in detail. Low professionalism and negligent performance of duties by officials appointed to the positions of heads of services and relevant officials are common causes of violations of poor records of military property in military services, which have led to losses, risks of illegal expenditures and shortages. military units assigned to support, which in their duties had to work out timely documents on the accounting of material values, spending according to the norms and write-off of military property, keeping books of losses and shortages. Today there is a question of introduction of effective system of the organization of internal audit and adaptation of its technique to activity of budgetary institutions including military units of Armed forces of Ukraine in the conditions of reforming and deepening of integration processes in economy of Ukraine.